Éducation, libéralisme et globalisation. Dialogue avec l’œuvre de Francis Fukuyama - Camille Roelens (Recherches en Éducation)
This article is based on the political philosophy of education and training and on the recent history of ideas in these same fields. We explore the hypothesis that the crises of education and training, especially in a globalized world, can best be understood through a more global reflection on liberalism and its own crises, tensions and problems. First, we clarify, refine, update and make our own this proposal. We then discuss this theme and its foundations with one of the most important theorists of the mutations and challenges of liberalism in globalization, namely Francis Fukuyama, and attempt to highlight the educational and formative stakes of his main theses.